Anti-tumor activity of N-trimethyl chitosan-encapsulated camptothecin in a mouse melanoma model - Liu, Xian-ping (BioMed Central, 2010)
BACKGROUND: Camptothecin (CPT) has recently attracted increasing attention as a promising anticancer agent for a variety of tumors. But the clinical application is largely hampered by its extreme water insolubility and unpredictable side effect. It is essential to establish an efficient and safe protocol for the administration of CPT versus melanoma. METHODS: Camptothecin was encapsulated with N-trimethyl chitosan (CPT-TMC) through microprecipitation and sonication. Its inhibition effect on B16-F10 cell proliferation and induction of apoptosis was evaluated by MTT assay and flow cytometric analysis in vitro. The anti-tumor activity of CPT-TMC was evaluated in C57BL/6 mice bearing B16-F10 melanoma. Tumor volume, tumor weight and survival time were recorded. Assessment of apoptotic cells within tumor tissue was performed by TUNEL assay. Antiangiogenesis and antiproliferation effects of CPT-TMC in vivo were conducted via CD31 and PCNA immunohistochemistry, respectively. RESULTS: CPT-TMC efficiently inhibited B16-F10 cells proliferation and increased apoptosis in vitro. Experiment group showed significant inhibition compared with free CPT-treated group (81.3% vs. 56.9%) in the growth of B16-F10 melanoma xenografts and prolonged the survival time of the treated mice (P < 0.05). Decreased cell proliferation, increased tumor apoptosis as well as a reduction in angiogenesis were observed. CONCLUSIONS: Our data suggest that N-trimethyl chitosan-encapsulated camptothecin is superior to free CPT by overcoming its insolubility and finally raises the potential of its application in melanoma therapy.